COMPUTATIONAL ANALYSIS OF PROTEIN SEQUENCES IN RESPECT TO THEIR PHYSIOCHEMICAL PROPERTIES ACCOMPANYING STRUCTURAL DIFFERENCES IN EXO AND ENDOPOLYGALACTURONASES ACTIVITY - V. KUMARI; N.SHARMA; T.C. BHALLA (International Journal of Pharma and Bio Sciences, 2013)
Polygalacturonases (exo and endopolygalacturonases) belong to glycoside hydrolases family 28 of CAZy (carbohydrate active enzyme database) glycoside hydrolases (GHs), a diverse yet phylogenetically and structurally related gene family that degrades pectin in a variety of ways. This study deals with computational analysis of primary structure of exo and endopolygalacturonase from plants, fungal and bacterial sequences with respect to their physiochemical properties leading to differences in mode of action. Multiple sequence alignment of amino acid sequences revealed clear differences between exo and endopolygalacturonases. The N-terminal end of exopolygalacturonases is blocked by formation of high-rising wall by position specific presence of certain amino acids (Asp, Asn, Gly, Trp, Phe, Tyr, Gln and Leu), which were found to be conserved near the active site and N-terminal region of exopolygalacturonases. Formation of high-raising wall results in exo the mode of activity. Statistical analysis of the physiochemical properties showed significant differences in number of amino acids, negatively and positively charged residues, extinction coefficient and instability index of both the polygalacturonases. The percentage composition of Arg, Glu, Leu, Met, and Pro were significantly higher in exopolygalacturonases while percentage is higher in endopolygalacturonases. The phylogenetic tree reflected that plant; fungal, bacterial enzymes formed their own cluster with the distinction of exo and endo mode of action.